The Destructive Sublime in Tamburlaine the Great - Algamdi, Kholoud (International Journal of Language and Literary Studies, 2023)
The subject of this essay is not a response that depends on the religious or moral conventions that are usually invoked by critics, but rather it is a vision that echoes destructive sublime in Tamburlaine’s character, arousing another kind of sublimity from representations of feminine forms. The request for a precise societal appreciation is produced from the ‘new immaterial’ world, which was represented in entity of the bloody Tamburlaine who found himself profaned in the ‘human’ world through his sense of destructive sublimity, as it will be discussed later. In Marlowe’s play Tamburlaine the Great, I will investigate how the sublime, as a representative of destructiveness and violence, being shaped over a kind of displeasure with the outer world and within the self. Moreover, I will argue how the female figure in this play is the ‘object petit’, introducing the lack, the otherness of femininity which ultimately incapacitates the male protagonist.